Human–Technology Choreographies: Body, Movement, and Space - Pirhonen, Antti; Tuuri, Kai; Erkut, Cumhur (Human Technology, 2016)
In interaction design and related disciplines, the focus of research tends toward technological objects rather than the movements relating to interacting with the objects. Even when movements are considered, the emphasis is placed on their instrumental value, that is, how movements have direct effect on the functions of technology. However, the emphasis of this thematic issue of Human Technology rests upon the design and use of technological objects. In other words, we, as editors of this special issue, were looking for submissions that emphasized intentional human movement in the physical and social lifeworld in which humans encounter technological and virtual artifacts.